Baitul Maal wat Tamwil (BMT) Sebagai Instrumen Moneter Inklusif untuk Pembangunan Berkelanjutan (SDGs) - Fikri, Muhammad Luthfi Ali; Mustofa, Ahmad Junaydi; Lail, Ibnaty Hidayatul; Nabila, Firzanah Uma; Hidayati, Amalia Nuril (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Baitul Maal wat Tamwil (BMT) is an Islamic microfinance institution that plays an essential role in expanding financial access for low-income communities and supporting sustainable economic development. This article aims to analyze the role of BMT as an inclusive monetary instrument within the framework of the Sustainable Development Goals (SDGs). The study employs a library research approach with descriptive-analytical methods based on secondary data from books, academic journals, research reports, and official documents. The findings show that BMT significantly contributes to financial inclusion through real-sector-based Islamic financing, especially for micro-enterprises and low-income households. Moreover, BMT’s social function—realized through the management of zakat, infaq, and sadaqah—strengthens income redistribution, poverty alleviation, and community welfare. BMT supports several SDG targets, particularly in reducing poverty, creating decent employment, developing MSMEs, and minimizing socioeconomic inequality. However, the optimization of BMT’s role still faces challenges such as limited capital, governance constraints, digital transformation, and institutional strengthening. Therefore, synergy between BMT, the government, regulators, and the community is needed to enhance BMT’s contribution as an inclusive, sustainable, and Sharia-compliant economic development agent.